Acquirement of Land Rights by Foreign Investors: An International Investment Law Perspective - Szilágyi, János Ede; Kovács, Bálint (Acquisition of Agricultural Lands, 2022)
This chapter provides an insight into the world of international investment law and its intersection with cross-border acquirement/acquisition of land. Cross-border acquirements, in this context, can be viewed as foreign investments that may fall under the protection of one (or more) of the approximately 3,000 existing international investment agreements. International investment law, as a complex and autonomous system, provides protection to investors via substantive provisions and investment treaty arbitration. The unique situation of Central Europe within this particular international law framework is something which merits attention, which is why this chapter provides an introductory part for the reader to gain a general knowledge of the field and then dives into some of the regional specificities, in tune with the rest of the book.Keywords: international investment law, arbitration, land acquisition, land grabbing